2D non‐polarising transmission filters based on GMR for optical communications. (1st November 2018) - Ren, Zhibin; Sun, Yahui; Zhang, Shuqing; Zhang, Kaipeng; Lin, Zihao; Wang, Songli
Abstract : Two‐dimensional (2D) non‐polarising transmission filters based on guided‐mode resonance (GMR) for the optical communication wavelength O‐band and C‐band have been designed and fabricated. This type of GMR filter (GMRF) is composed of a 2D metal grating layer, a waveguide layer, and a glass substrate. The rigorous coupled‐wave analysis is used to calculate the transmission spectra of the designed GMRFs. The grating structures of the GMRFs are patterned by electron beam lithography. The transmission spectra of the fabricated GMRF samples at different incident angles are measured by rotating a motorised stage and the experimental results agree closely with the theoretical designs. The measured results show that the transmission spectra of the two GMRF samples are insensitive to the incident angle. A deviation of 1° in the angle of incidence from normal illumination does not lead to the reduction of the peak transmittance. Although a narrow secondary resonance appears at oblique incidence for transverse‐magnetic polarisation, the resonance spectral shapes for transverse‐electric polarisation and TM polarisation are nearly identical at incident angles of 0–1.5°. Compared to previous reported non‐polarising GMRFs, the angular tolerances of the fabricated samples are remarkably enhanced.